THE INFLUENCE OF COMPETENCE AND JOB PLACEMENT ON THE PERFORMANCE WITH WORK DISCIPLINE AS A MODERATING VARIABLE - Candra Susila; Sardiyo Sardiyo; Sutanta Sutanta (LPPM UNIVERSITAS BINA INSAN, 2025)
This research investigates the Financial and Asset Management Agency of Lubuklinggau City to elucidate the independent variable's influence on the dependent variable while simultaneously assessing the moderating variable's role. The study surveyed a purposive sample of 57 agency employees. Data were scrutinized via Moderated Regression Analysis (MRA). The principal findings are as follows: 1) Employee performance registers a statistically significant partial correlation with employee competence. The correlation manifests through a t statistic of 4.926, which exceeds the critical t value of 2.002, a significance level of 0.000 (p < 0.05), and a standardized coefficient of 0.516. Competence emerges as the preeminent explanatory variable. 2) Employee performance likewise correlates positively with employee motivation, the latter being observable through collegial interactions and the conferment of recognition. 3) Work discipline functions as a moderating variable that intensifies the relationship between competence and employee performance, evident in a t statistic of 2.399 (t critical = 2.002), a significance of 0.003 (p < 0.05), and a coefficient of 0.285. The interplay of heightened competence and clearly delineated performance objectives cultivates self-regulated discipline among the workforce. 4). The root-norm of work discipline significantly magnifies the effect of the task-allocation parameter on the output of personnel, as the statistically determined t value of 2.382 exceeds the tabulated t criterion of 2.002, with a significance level of .007, thus remaining below the .05 threshold, and yielding a regression coefficient of .273. Sustained evaluative supervision thereby emerges as the foundational support for the efficacy of the process intended to institutionalize the observance of discipline.